Implementation of the Principles of Efficiency and Transparency in Management of Local Original Revenue (Pad): JEL Classification: H72, H83, O23, Z32, L83 - Nursalam Nursalam; Nurmadhani Fitri Suyuthi; St Rukaiyah (Journal La Bisecoman, 2026)
The implementation of efficiency and transparency principles in the management of Regional Original Revenue (PAD) is a crucial aspect of promoting good governance, particularly in the tourism sector. At the Department of Culture and Tourism of North Toraja Regency for the 2024 fiscal year, efficiency is reflected in the optimization of resources and the digitization of tourism retribution services, while transparency is demonstrated through public information disclosure and the preparation of accountable financial reports. However, efforts to develop the tourism sector as a driver of PAD remain constrained by several challenges, including limited funding, the absence of clear regulations on tourism retribution, and weak support for information system infrastructure. Additional technical barriers include uneven human resource capacity, complex asset management, and suboptimal coordination among stakeholders. To address these issues, the Department has formulated responsive strategies, such as strengthening financial literacy, establishing coordination forums among regional work units (SKPD), enhancing accounting-based information systems, conducting regular monitoring, and providing technical training for staff. Overall, the effectiveness of implementing efficiency and transparency principles is determined by institutional synergy, modernization of financial management systems, and shared commitment in managing local revenue potential in a sustainable manner.